Morphofunctional indicators demonstrated by young students resident in Russia’s Northeast - Averyanova, I. V.; Maksimov, A. L.; Vdovenko, S. I. (Regulatory Mechanisms in Biosystems, 2017)
The specific climatic and geographical conditions of the northern territories of Russia, the relatively small workforce, as well as intensive migration processes require a specific approach with regard to northern regions and, particularly, to the healthcare of the young generation residing in the territory. This study was aimed at exploring the body functionality of the young inhabitants of Russia’s Northeast considered as a human rescource for the future in relation to their period of residence in Magadan oblast. Based on the study of cardiovascular, biochemical, lipid and carbohydrate metabolism, psychophysiological characteristics, as well as respiratory system and gas exchange parameters, a comparative examination was carried which involved 1,560 male students aged 17–21. Depending on their period of residence in Magadan oblast, the examined subjects were divided into three groups. Group 1 was presented by newcoming settlers, whites by origin (adaptants), who had migrated from the Central-European or Asian areas of Russia and lived in the northern region for at least 5 years (the zero generation). Group 2 was made up of those young males born and living in Magadan oblast (the 1st generation), whites by origin, who were children of immigrants to the area. Finally, group 3 was representatives of the 2nd generation born and living in Magadan oblast, whose parents were representatives of the 1st generation. We found that people with a longer term of residency in the north had become more optimized in cardiovascular functioning (demonstrate decrease in arterial pressure and more effective myocardial performance), less stressed in external respiration with simultaneous decrease in exhaled heat loss, had normalised lipid metabolism shown through a reduced percentage of deviations in lipidograms as well as the index of atherogenicity and higher functioning of the central nervous system. Besides, having experienced severe climatic conditions they have formed their specific region-related metabolic profile featuring lowered lipid metabolism values and high blood glucose which can be caused by changes in nutrition of city residents. It should be concluded that discovered tendency of adaptive changes demonstrated by north-born young white males enables us to consider it as formation of a new population of inhabitants of the North having the best functional abilities for optimal adaptation to the specific ecological and climatic conditions.